The Iraq War : A Military History - Murray, Williamson and Scales, Robert H. (London Harvard University Press, 2005)
An in-depth analysis of the coalition invasion of Iraq, up to the 2003 fall of Baghdad. Drawing on their extensive expertise as military historians, the authors assess the opposing aims of the Coalition forces and the Iraqi regime and explain the day-to-day tactical and logistical decisions of infantry and air command, as British and American troops moved into Basra and Baghdad. They simultaneously step back to examine long-running debates within the U.S. Defense Department about the proper uses of military power and probe the strategic implications of those debates for America's buildup to this war. Surveying the immense changes that have occurred in America's armed forces between the Gulf conflicts of 1991 and 2003 -- changes in doctrine as well as weapons -- this volume reveals critical meanings and lessons about the new "American way of war" as it has unfolded in Iraq.
Include Maps and Index
Keywords: Iraq War, 2003-2011 -- United States -- Armed Forces -- History -- 21st century